The Psychology Impact of visual art (Al-Academy, 2025)
The history of psychotherapy through art (specifically, visual arts) is considered one of the ancient methods with historical references from the beginnings of visual arts. This connection is evident through the history of arts extending back to the Stone Age in many regions such as Asia, Africa, Spain, and some regions where the first fingerprints of expression were found through visual arts. Modern medicine and modern philosophies have come with various encouragements and prohibitions of drug practices and chemical drugs for treatment and benefit from treatment through art. Expression through various artistic means and tools, including shape, colour, line, and light, as well as the ability to employ different materials such as paper and raw materials with safe handling. Human practices and human interaction with them are linked according to human needs and finding ways to benefit from employing materials from nature and harnessing them to serve him first and add aesthetic pleasure on the other hand. The researcher found it necessary to shed light on this axis and reveal ways to employ art in psychological treatments and.